Evidence-based assessment of the efficacy and effectiveness of light/laser activation in in-office dental bleaching - Reem A Ajaj; Francesco Chiappelli; Linda Phi; Amy Giroux; Carl Maida; Neal Garrett; Olga Polinovsky (Dental Hypotheses, 2012)
Many in-office bleaching techniques use the light/laser in conjunction with the bleaching agent claiming more favorable bleaching results. Controversy still exists in the literature as to the role of a light/laser in bleaching results. The goal of this study is to determine, through Comparative Effectiveness-Efficacy Research and Analysis for Practice (CEERAP), if the co-use of light/laser activation with the chemical bleaching agent has improved teeth whitening compared to using the chemical bleaching agent alone. Systematic reviews and randomized clinical trials on the research question were obtained using multiple search engines. Assessment of the level and quality of evidence and acceptable sample analysis were performed for the Randomized Clinical Trials (RCTs). Due to heterogeneity of the acceptable studies, meta-analysis was performed only on the two most homogenous studies. Qualitative assessment of the acceptable studies was performed. The strength of clinical recommendation was assessed. Only one qualitative systematic review was found. Eight articles were accepted as high quality RCTs. The meta-analysis shows preferable outcome when using the light activation with the bleaching material than when using the bleaching material alone. Qualitative assessment of the acceptable studies shows conflicting results. Most studies agreed that the use of light is proven to increase the whitening effect of the bleaching agent, especially for a short term after treatment. Additional studies with greater consistency in methodology and outcomes are needed to be able to reach a definite consensus regarding the effectiveness of using light during bleaching through an overarching meta-analysis for more powerful statistical results.